2003
DOI: 10.1091/mbc.e03-03-0160
|View full text |Cite
|
Sign up to set email alerts
|

Arfophilins Are Dual Arf/Rab 11 Binding Proteins That Regulate Recycling Endosome Distribution and Are Related toDrosophilaNuclear Fallout

Abstract: Arfophilin is an ADP ribosylation factor (Arf) binding protein of unknown function. It is identical to the Rab11 binding protein eferin/Rab11-FIP3, and we show it binds both Arf5 and Rab11. We describe a related protein, arfophilin-2, that interacts with Arf5 in a nucleotide-dependent manner, but not Arf1, 4, or 6 and also binds Rab11. Arfophilin-2 localized to a perinuclear compartment, the centrosomal area, and focal adhesions. The localization of arfophilin-2 to the perinuclear compartment was selectively b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
163
0
4

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 138 publications
(174 citation statements)
references
References 37 publications
7
163
0
4
Order By: Relevance
“…FIP3 preferentially binds to Arf6 and Arf5 (Shin et al, 2001;Hickson et al, 2003;Fielding et al, 2005). We found FIP3 interaction stimulates ASAP1 GAP activity against Arf1, but not against Arf6.…”
Section: Discussionmentioning
confidence: 64%
“…FIP3 preferentially binds to Arf6 and Arf5 (Shin et al, 2001;Hickson et al, 2003;Fielding et al, 2005). We found FIP3 interaction stimulates ASAP1 GAP activity against Arf1, but not against Arf6.…”
Section: Discussionmentioning
confidence: 64%
“…2d) similar to certain RE proteins involved in vesicle trafficking during cytokinesis (19,20). Costaining of cells with ␣-tubulin revealed that RalA localized predominantly to the plasma membrane in mitosis, during which endosome recycling stops.…”
Section: Resultsmentioning
confidence: 83%
“…Consistent with this idea, different FIPs are reported to interact with distinct sets of proteins that are known to regulate various endocytic pathways. For instance, FIP2 interacts with myosin Vb, whereas FIP3 and FIP4 bind to ADP-ribosylation factor GTPases, thereby generating putative Rab11⅐FIP2⅐myosin Vb or Rab11⅐FIP3⅐ADP-ribosylation factor complexes to regulate different transport steps and/or pathways (17,27).…”
Section: Fig 7 Mutational Analysis Of the Conserved Rbd Of Fipsmentioning
confidence: 99%
“…Recently, several Rab11 effector proteins, Rip11, FIP2, 1 Rab-coupling protein (RCP), FIP3/eferin, and FIP4, were identified using biochemical and yeast two-hybrid methods (12)(13)(14)(15). In addition to Rab11 binding, FIP3 and FIP4 also interact with ADP-ribosylation factor GTPases, thereby coupling these small GTPase families, allowing for potential cross-talk between two signaling pathways (17). All FIPs have a conserved C-terminal motif that is known as the Rab11/25-binding domain (RBD) (18).…”
mentioning
confidence: 99%